PROFIL PEMECAHAN MASALAH MATEMATIKA SISWA DITINJAU DARI GAYA KOGNITIF FIELD DEPENDENT DAN FIELD INDEPENDENT - Resty Tirta Risani; SITI NURIYATIN (JEDMA Jurnal Edukasi Matematika, 2021)
This study aims to describe the profile of students' mathematical problem solving in terms of the field dependent and field independent cognitive styles. This type of research was descriptive qualitative research. The study was conducted at SMP Negeri 1 Candi in 2018/2019 school year. Determination of the subject based on the acquisition of the results of GEFT (Group Embedded Figures Test) test questions given to students in order to classify students' cognitive style types. The subjects used in this study were 2 students taken from class VIII-E, which 1 students are with independent field cognitive style with GEFT test scores between 13 and 15 and 1 students are with field dependent cognitive style with a score of GEFT test results between 4 up to 6. The social arithmetic problem solving test is given to see the problem solving of the subject in solving problems. The results showed a significant difference between the two subjects in implementing the completion plan, namely the field independent subjects were able to carry out the completion plan better by linking information from the questions and formulas used for determine the answer when compared with the field dependent subject. In addition, the independent field subject showed a good understanding to determine each final result of the calculation of fractional and decimal forms when compared to the field dependent subject.